Diagnosis of severe growth hormone deficiency in the newborn. (29th June 2020) - Binder, Gerhard; Weber, Karin; Rieflin, Nora; Steinruck, Louis; Blumenstock, Gunnar; Janzen, Nils; Franz, Axel R.
Abstract: Objective: Severe neonatal growth hormone deficiency (GHD) can cause recurrent hypoglycaemia. Early diagnosis is warranted. The aim of the study was to analyse the GH content in screening cards of 25 affected and 281 healthy newborns. Patients and Measurements: A total of 110 screening cards from ill newborns were sent to us for measuring GH content by a highly sensitive GH ELISA. Clinical information was obtainable in 61 cases. Severe GHD was defined by the presence of recurrent hypoglycaemia with a significant pituitary malformation or two additional pituitary hormone deficiencies. Screening cards from 281 healthy newborns (34.0‐37.9 weeks) were prospectively analysed. Results: In 25 newborns (5 preterm), the definition of severe GHD was fulfilled based on recurrent hypoglycaemia in combination with malformation of the pituitary or midline structures in 21 cases and combined TSH and ACTH deficiency in four cases. The median GH concentration of those affected with severe GHD was 3.9 µg/L (range: 1.1‐11.8), significantly below the previously reported reference range ( P < .001). A GH concentration of 7 µg/L was confirmed as the cut‐off for term newborns with the best accuracy (90.0% sensitivity and 98.7% specificity). The 95% reference range for healthy preterm newborns (n = 151) was 7.6‐47.1 µg/L (median: 20.3 µg/L). Conclusions: A GH content <7.0 µg/L in the newborn screening card confirms severe GHD with high accuracy. In preterm newborns, the lower limit of the reference interval was 0.6 µg/L higher than in term newborns. The newborn screening card is a valuable source for the very early diagnosis of GH deficiency.